An Analysis of Women's Language Used in the Movie Encanto - Sukma, Wahdini Wilyandri; Fitrawati, Fitrawati (English Language and Literature, 2023)
This study concerns with women’s language used in the movie Encanto. The aims of the study were to find out the use of women’s language features and language functions of women’s language used by female characters in the movie Encanto. The utterances of female characters were analyzed by using Lakoff’s women’s language theory and Jakobson’s language function theory. Qualitative method used in this study to analyzing the data and describe the findings. There were 65 utterances from eight features of women’s language features that occurred in the movie Encanto. They were 15 lexical hedges or fillers, 14 intensifiers, 6 rising intonations, 3 ‘empty’ adjectives, 12 emphatic stress, 8 tag questions, 5 ‘superpolite’ forms, and 2 avoidance of strong swear words. Lexical hedges or fillers came out as the most dominant feature of women’s language features used in the movie Encanto. Then, the kinds of language function used by female characters in the movie Encanto were expressive function, directive function, referential function, metalinguistic function, and phatic function. The most dominant language function used by female characters in the movie Encanto was expressive function.